Synthesis of Polysubstituted Analogues of the 4-Methyl-2-phenylquinoline - Al-Qahtani, A.A.; Al-Turki, T.M.; Khan, M.; Mousa, A.A.; Alkhathlan, H.Z. (Asian Journal of Chemistry, 2013)
A simple and convenient synthetic method for the direct synthesis of a series of polysubstituted analogues of the putative antifungal agent 4-methyl-2-phenylquinoline, a mimic of the natural bioactive 4-methoxy-2-phenylquinoline is reported.